Answer:
Now, I ain't tryin' to sound mean or standoff-ish but I'm pretty sure Wikipedia could answer this question for you
Answer:
2(5x - 1) – (2x - 5)
=2(5x−1)−2x+5
=10x−2−2x+5
=(10x−2x)+(−2+5)
=8x+3
Step-by-step explanation:
Answer:
17, 19, 21
Step-by-step explanation:
If we denote the smallest number as x, then the middle number will be x + 2 and the largest number will be x + 2 + 2.
The equation is:
x + (x + 2) = 3 * (x + 2 + 2) - 27
2x + 2 = 3x + 12 - 27
2x - 3x = 12 - 27 - 2
-x = -17
x = 17
The numbers are: 17, 19, 21
Let's check to be sure:
17 + 19 = 36
3 * 21 - 27 = 63 - 27 = 36
( - 45, 0)
to find the x-intercept let y = 0 in the equation
x = 0 → x = - 15
multiply both sides by 3
x = 3 × - 15 = - 45
x-intercept = ( - 45, 0)
Answer:
I had to repost my answer because i got deleted from some reason
Step-by-step explanation: